EFFECT ON ACADEMIC PERFORMANCE BY LEARNING ONLINE THROUGH 3D ANATOMY ATLAS VERSUS 2D PRESENTATIONS: 3d Anatomy Atlas Versus 2d Presentations - Haque, Ayesha; Minhas, Ruqqia Shafi; Faisal, Tayyaba; Naseem, Sajida; Ambreen, Salma; Rafi, Aisha (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the effect of using a 3-D atlas on academic performance and compare it with the use of power point presentations during online lectures for gross anatomy of the head. Study Design: Comparative prospective study. Place and Duration of Study: Department of Anatomy, Dental College, Heavy Industries Taxila Education City Institute of Medical Sciences, Taxila Pakistan, from Jun to Jul 2020. Methodology: Forty-nine students from first year BDS were selected through nonprobability convenience sampling. They were assigned to two groups, A and B comprising of 25 and 24 students respectively. Group A was taught gross anatomy of head region via Zoom lectures employing a digital three-dimensional anatomy atlas application (Visual body, 2019). Group B was exposed to only two-dimensional pictures through presentations during their lectures. Ten teaching sessions were conducted with post session MCQ based assessments. One comprehensive assessment was conducted at the completion of the region. Results were compared for both groups. Results: The mean scores for three of the post session assessment tests were higher for group A (15.72 ± 2.03, 15.28 ± 2.79, 16.92 ± 2.13) as compared to that of group B (14.64 ± 3.42, 13.66 ± 3.00, 15.04 ± 3.01) (p<0.05). Similarly, the mean score for comprehensive assessment for group A (35.36 ± 6.02) was also more than that of group B (31.41 ± 6.88) (p<0.05). Conclusion: Three-dimensional viewing of structures led to better academic performance as compared to that of presentations with two dimensional pictures.